(untitled) (Journal of Sciences & Technology, 2016)
The aim of this paper is to review and evaluate the performances of a solar tower gas turbine central with a capacity of 11.5 MWe, then we assess the potential to improve the capacity of the installation by adding a combined steam cycle with electrical production equal to 3.5.The numerical study of the installation will be done by calculating the solar fields’ effectiveness, and then we simulate the different components of the installation by the TRNSYS 16 software. The aim of this paper is to review and evaluate the performances of a solar tower gas turbine central with a capacity of 11.5 MWe, then we assess the potential to improve the capacity of the installation by adding a combined steam cycle with electrical production equal to 3.5.The numerical study of the installation will be done by calculating the solar fields’ effectiveness, and then we simulate the different components of the installation by the TRNSYS 16 software.